2021
DOI: 10.1177/1352458521988926
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of the primary endpoint from the N-MOmentum study of inebilizumab in NMOSD

Abstract: Background: In the N-MOmentum trial, the risk of an adjudicated neuromyelitis optica spectrum disorder (NMOSD) attack was significantly reduced with inebilizumab compared with placebo. Objective: To demonstrate the robustness of this finding, using pre-specified sensitivity and subgroup analyses. Methods: N-MOmentum is a prospective, randomized, placebo-controlled, double-masked trial of inebilizumab, an anti-CD19 monoclonal B-cell-depleting antibody, in patients with NMOSD. Pre-planned and post hoc analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Sensitivity analyses to test robustness of the primary endpoint were carried out in the PREVENT and N-MOmentum trials and corroborated the primary outcomes. 4,9 Inebilizumab also diminished the risk of 3-month confirmed disability progression independent of baseline features of the disease. 10 Importantly, there were differences regarding aquaporin-4 IgG serostatus.…”
mentioning
confidence: 90%
“…Sensitivity analyses to test robustness of the primary endpoint were carried out in the PREVENT and N-MOmentum trials and corroborated the primary outcomes. 4,9 Inebilizumab also diminished the risk of 3-month confirmed disability progression independent of baseline features of the disease. 10 Importantly, there were differences regarding aquaporin-4 IgG serostatus.…”
mentioning
confidence: 90%
“…Due to the sample’s inequality regarding seronegative patients among groups (only four participants were randomized to the placebo arm), efficacy could not be interpreted in the seronegative subset. Of note, the trial also confirmed that the efficacy of inebulizumab was consistent across the clinical presentations of myelitis and optic neuritis domains [ 138 , 139 , 140 ].…”
Section: Emerging Therapeutic Approachesmentioning
confidence: 71%
“…Furthermore, among AQP4-seropositive patients, fewer had a statistically significant worsening of their EDSS score. The inebilizumab arm also had lower numbers of cumulative active MRI lesions and NMOSD-related hospitalizations compared with the placebo [ 139 , 140 , 141 ]. Serious adverse events were similar among both the inebulizumab (9%) and placebo groups (5%); however, 2% of patients on the agent developed transient grade 3 neutropenia.…”
Section: Emerging Therapeutic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…In other subgroup analyses, inebilizumab showed significant relapse inhibition compared to those given placebo regardless of the site of relapse, disease duration, number of relapses in the previous 6 mo, number of relapses since onset, baseline EDSS, race, weight, and previous immunosuppressive treatment, including rituximab. [45][46][47] In a continuation study, 201 AQP4 antibody-positive patients received inebilizumab (300 mg) every 26 wk, of which 75 patients had received the drug for more than 4 y. 48 In this report, 18 relapses were identified after the initiation of inebilizumab (annual relapse rate, 0.052), 12 of which (67%) occurred within 1 y of starting inebilizumab treatment, and four of the five severe relapses occurred within 1 y of starting inebilizumab treatment.…”
Section: Efficacymentioning
confidence: 99%